LEMBAGA PENDIDIKAN ISLAM KLASIK DI NUSANTARA (Studi Terhadap Surau, Meunasah Dan Pesantren) - budi FITK (Hijri, 2018)
Islam is the most important component in shaping and coloring pattern of life of the community. Education is one that gets a significant impact from the spread of Islam. The development of Islamic education in Indonesia, among others, marked by the emergence of various educational institutions in stages, ranging from the very simple to the already uncountable modern and complete. One of the places of learning in the early days of the Islamic position on the Nusatara is a boarding school, though much earlier had there are places of learning that starts from the surau, or musalla meunasah dayah, rangkang, and so on. Until now, the Islamic educational institutions have a pivotal role against the pattern of religion society of Indonesia. Keyword: Institution, Education, Islam, Nusantara